Lake Michigan's suitability for bigheaded carp: The importance of diet flexibility and subsurface habitat. (12th August 2019) - Alsip, Peter J.; Zhang, Hongyan; Rowe, Mark D.; Mason, Doran M.; Rutherford, Edward S.; Riseng, Catherine M.; Su, Zhenming
Abstract: As bighead ( Hypophthalmichthys nobilis ) and silver carp ( Hypophthalmichthys molitrix )—collectively bigheaded carp (BHC)—arrive at Lake Michigan's doorstep, questions remain as to whether there is sufficient food to support these invasive filter‐feeding fishes in the upper Laurentian Great Lakes. Previous studies suggest that suitable BHC habitat is limited to a few productive, nearshore areas. However, those studies did not consider the influence of BHC's diet plasticity or the presence of spatially‐discrete subsurface prey resources. This study aimed to characterise Lake Michigan's suitability for BHC and evaluate the importance of these considerations in habitat suitability assessments. We used simulated outputs of prey biomass (phytoplankton, zooplankton, and detritus) and water temperature from a three‐dimensional biophysical model of Lake Michigan to evaluate growth rate potential (GRP, quantitative index of habitat suitability) of adult BHC throughout the entire volume of the lake. Our GRP model applied a foraging model and a bioenergetics model to translate prey concentrations and water temperatures into habitat quality indexed by individual fish growth rate. We defined suitable habitat as habitats that can support GRP ≥ 0 g g −1 day −1 . We developed six feeding scenarios to evaluate the impact of diet flexibility and subsurface prey resources on suitable habitat quantity. Scenarios were defined by the number of prey types the fish could consume and the depths at which they could feed (surface or whole water column). Consistent with previous studies, we found that habitats with the highest quality were concentrated near river mouths and in eutrophic areas of Green Bay. However, in contrast to previous studies, we found suitable offshore habitat for bighead carp owing to our added considerations of diet plasticity and subsurface prey resources. For silver carp, these considerations extended suitable habitat within Green Bay and in some tributary‐influenced nearshore areas, but offshore areas remained predominantly unsuitable in all feeding scenarios. Differences in simulated habitat suitability between these two species probably reflect differences in energy density and mass of the specific fishes we used in our model. However, reports of these two species in environments where they coexist indicate that bighead carp grow at faster rates than silver carp, as our model simulated. Our vertical analysis at Muskegon, MI, U.S.A. indicates that subsurface temperature and prey biomass are not only sufficient to support bighead carp growth but provide maximum habitat quality during late summer stratification. Overall, our study demonstrates that BHC are capable of surviving and growing in much larger areas of Lake Michigan than predicted by previous studies, and thus suggests that the risk of establishment is not sufficiently reduced by low plankton concentrations. Maps generated by our model identified the potential for cross‐lake migration corridors that may facilitate and accelerate lake‐wide movements. We believe these maps could be used to prioritise surveillance protocols by identifying areas to which BHC might spread upon entering the lake. More broadly, this research demonstrates how the physiology and trophic ecology of BHC contributes to their high invasive capacity and can permit their survival in novel environments.